Modulation of gut microbiota and intestinal immune response in gilthead seabream (Sparus aurata) by dietary bile salt supplementation - Ruiz, Alberto; Andree, Karl B.; Furones, Dolors; Holhorea, Paul G.; Calduch-Giner, Josep À.; Viñas, Marc; Pérez-Sánchez, Jaume; Gisbert, Enric (Frontiers in Microbiology, 2023)
Given their role in lipid digestion, feed supplementation with bile salts could be an economic and sustainable solution to alterations in adiposity and intestinal inflammation generated by some strategies currently used in aquaculture. An important part of the metabolism of bile salts takes place in the intestine, where the microbiota transforms them into more toxic forms. Consequently, we aimed to evaluate the gut immune response and microbial populations in gilthead seabream (Sparus aurata) fed a diet supplemented with a blend of bile salts with proven background as a regulator of lipid metabolism and fat content. After the 90-day feeding trial, a differential modulation of the microbiota between the anterior and posterior intestine was observed. While in the anterior intestine the relative abundance of Desulfobacterota doubled, in the posterior intestine the levels of Firmicutes increased and Proteobacteria, Actinobacteriota, Campylobacterota were reduced when supplementing the diet with bile salts. Even so, only in the anterior intestine there was a decrease in estimated richness (Chao1 and ACE indices) in presence of dietary bile salts. No significant differences were displayed in alpha (Shannon and Simpson indices) nor beta diversity, showing that bile sales did not have a great impact on the intestinal microbiota. Regarding the gene expression profile in 2 h postprandial-fish, several changes were observed in the analysed biomarkers of epithelial integrity, nutrient transport, mucus production, interleukins, cell markers, immunoglobulin production and pathogen recognition receptors. These results may indicate the development of an intestinal immune-protective status to tackle future threats. This work also suggests that this immune response is not only regulated by the presence of the dietary bile salts in the intestine, but also by the microbial populations that are in turn modulated by bile salts. After a fasting period of two days, the overall gene expression profile was stabilized with respect to fish fed the unsupplemented diet, indicating that the effect of bile salts was transient after short periods of fasting. On the balance, bile salts can be used as a dietary supplement to enhance S. aurata farming and production without compromising their intestinal health.